The Financial Analysis of Food Barn Based on SAK EMKM Pendem Village, Junrejo District, Batu City - Romana Abon Nilan; Gunawan, Cakti Indra; Suhendri, Hendrik (International Research & Development for Human Beings (IRDH), 2025)
The study of food barns is an important matter to be conducted, especially to provide input to the government, which is currently intensively implementing the national food security program. This research aims to determine how the financial reports prepared by the Wiji Aji Bu farmer group manage the food barn to support food security at the rural level in the future. This study was conducted at the food barn in Pendem village, Junrejo district, Batu city, using a descriptive qualitative approach. The data collection methods employed observation, interviews, and documentation techniques. The informants in this research are members of the Wiji Aji Bu farmer group. The results of this study indicate that (1) the financial reports prepared are still simple, covering only cash inflows and outflows; (2) the preparation of financial reports at the food barn has not yet followed the financial accounting standards (SAK EMKM), but the managers state that they continue to maintain financial stability to ensure food security in Batu city.